2008
DOI: 10.1186/bcr1872
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box transcription factor FOXO3a suppresses estrogen-dependent breast cancer cell proliferation and tumorigenesis

Abstract: Introduction Estrogen receptors (ERs) play key roles in breast cancer development and influence treatment outcome in breast cancer patients. Identification of molecules that regulate ER function may facilitate development of breast cancer treatment strategies. The forkhead box class O (FOXO) transcription factor FOXO3a has been suggested to function as a tumor suppressor in breast cancer. Using protein-protein interaction screening, we found that FOXO3a interacted with ER-α and ER-β proteins in the human breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 44 publications
(61 reference statements)
10
127
2
1
Order By: Relevance
“…Instead, we found that subcellular localisation indicates functional relevance as evidenced here by more favourable outcome in patients with predominant nuclear expression. Supporting these findings, previous studies have shown that nuclear FOXO3a induces the expression of genes that inhibit cell cycle progression such as the CDK inhibitors [4,6]. Subsequently, we found a significant positive association between nuclear FOXO3a and the expression of the cell cycle inhibitor p27 implying a role in the induction of cell cycle arrest.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Instead, we found that subcellular localisation indicates functional relevance as evidenced here by more favourable outcome in patients with predominant nuclear expression. Supporting these findings, previous studies have shown that nuclear FOXO3a induces the expression of genes that inhibit cell cycle progression such as the CDK inhibitors [4,6]. Subsequently, we found a significant positive association between nuclear FOXO3a and the expression of the cell cycle inhibitor p27 implying a role in the induction of cell cycle arrest.…”
Section: Discussionsupporting
confidence: 76%
“…Zou et al 2008 [4] have reported that FOXO3a can suppress ERα-dependent breast cancer cell proliferation and tumourigenesis in the MCF-7 breast cancer cell line, suggesting a crosstalk between FOXO3a and ER signalling pathways in ER dependent breast cancer [4]. Other studies demonstrated FOXO3a has an important intracellular mediator role in ERα expression, suggesting possible therapeutic intervention [5].…”
Section: Introductionmentioning
confidence: 99%
“…They function in cell cycle arrest, differentiation and anti-oxidation response (Arden, 2008;Ho et al, 2008;Sedding, 2008). FOXO3 suppresses estrogendependent breast cancer cell proliferation and tumorigenesis (Zou et al, 2008). Triple deletion of FOXO1, FOXO3 and FOXO4 in somatic cells resulted in the formation of lymphoma (Paik et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have recently suggested a functional interaction between ER and FOXO family members. Estrogen-activated ER binds to FOXO1, FOXO3A, and FOXO4; which depending on the cellular context, exhibit co-activator or co-repressor functions on estrogen-responsive DNA regulatory elements (Schuur et al 2001, Zhao et al 2001, Zou et al 2008. Interestingly, ER has also shown to interact with a diverse number of FOX proteins including FOXE1 (Park et al 2012), FOXP1 (Halacli & Dogan 2015), and FOXA1 (Wright et al 2014); suggestive of a conserved mechanism of association between the receptor and the wider forkhead family.…”
Section: Interaction Between Foxos and Er Signalingmentioning
confidence: 99%
“…FOXO3A overexpression significantly inhibits the growth of breast tumors in vitro and in animal models (Hu et al 2004, Yang et al 2008, Zou et al 2008, and also negatively impacts upon angiogenesis; a process required for malignant tumor growth, invasion, and metastasis (Potente et al 2005). Hu et al (2004) observed that cytoplasmic FOXO3A staining correlated with the expression of inhibitor of nuclear factor kappa-B kinase subunit beta (IKKb), raised phospho-AKT and overall poorer patient survival.…”
Section: Foxos In Breast Cancermentioning
confidence: 99%